PEMERIKSAAN, PERAWATAN DAN SENAM PADA LANSIA DENGAN DIABETES MELLITUS DI UPT PUSKESMAS KOTA BUMI LAMPUNG UTARA TAHUN 2017 - Zainaro, M. Arifki; Djamaludin, Djunizar; Gunawan, M. Ricko; Susmarini, Neta (Universitas Malahayati Lampung, 2018)
ABSTRACTWorld Health Organization (WHO) data showed that Indonesia ranks 4th largest number of people with diabetes mellitus after India, China and the United States. In 2013 it was estimated that the number of diabetics in Indonesia has reached 14 million people, of which only 50% are aware of it and among them only about 30% who come for regular treatment. The objective of this activity is to increase knowledge people about the examination, treatment and foot gymnastic DM in people with diabetes mellitus. This activity was done on Monday, December 18, 2017. The activities consist of Examination, Treatment and Gymnastics Prolanis In Elderly with Diabetes Mellitus at UPT Puskesmas Kota Bumi Lampung Utara 2017 with the method was using leaflets and demonstrations. There was a change in the knowledge and techniques of prolanic gymnastics. Hope this prolanic exercise techniques of DM patients can reduce wounds in patients with DM. Keywords: Gymnastics, DM, Puskesmas.